LES FACTEURS DE RISQUE ASSOCIÉS À LA PRATIQUE DE CÉSARIENNE CHEZ LA FEMME ENCEINTE AU NIVEAU DE LA MATERNITÉ DE L’HÔPITAL IDRISSI DANS LA RÉGION DU GHARB MAROC - EL Bakkali, Mohamed; Azzouzi, Younes; Khadmaoui, Abderrazzak; Ahami, Ahmed Omar Thami; Boubel, Omar (European Scientific Journal, ESJ, 2014)
Identify risk factors for occurrence of cesarean section at Regional Hospital Sharif Idrissi in the Gharb region of Morocco. Analytical study of caesarean sections in the Regional Hospital Cherif Idrissi in the Gharb region during the study ranging from 01/04/2011 to 30/09/2011 period. These data were collected retrospectively using delivery records systematically established for each pregnant woman included. we analyzed the associated factors. we used as a statistical test coefficient and Yule Test ki-two for the analysis of contingency tables and multivariate logistic regression with a threshold of less than or equal to 5% significance. This study involved a total of 327 women of which 47 had caesarean, an incidence of 14,37%. We chose initially in univariate analysis as risk factors : 25.5% male ( p = 0,044 , OR = 1,93 ; Yule ’s Q = 0,32) , growth retardation to 46,2% (p = 0,013 , OR = 3,87 ; Yule ’s Q = 0,59) , age between 21-35 years to 23.3% (p = 0.048 , OR = 0.53 ; Yule ’s Q = 0.36) , having more than or equal to four delivery 21,7 % (p = 0.028 , OR = 3,69 ; Yule ’s Q = 0.57 ) and blood pressure amounted to 42.9% (p ≤ 0 05 , OR = 3,59 ; Yule ’s Q = 0,56) . Adjusted for other variables, the factors most strongly associated with the occurrence of cesarean section (positive relationship) are the number of higher birth or equal to 4 births (adjusted OR = 1,57 ; coeff.β = 0,45 , CI : 1,02-22,55 ) , low birth weight (OR = 3,84 ; coeff.β = 1,346 , CI : 1,009 - 14.618 ) and the age group between 21 and 35 years ( adjusted OR = 1,60 ; coeff.β = 0,47 IC : 0,084-6,486 ) . Instead normal blood pressure was found to be a protective factor (adjusted OR = 0,340 ; coeff.β = -1,08, CI: -3,127,- 0,055 ). The Caesarean section is streamlined in our series. However, cases are preventable if care is taken to ensure adequate monitoring of the pregnancy and the training, retraining and allocation in health facilities that support the mother and child of a qualified staffing maternity staff in equipment suitable for the treatment of pregnant women.